Sphingosine-1-phosphate lyase (SGPL1) deficiency is associated with mitochondrial dysfunction - GÜRAN, TÜLAY (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Deficiency in Sphingosine-1-phosphate lyase (S1P lyase) is associated with a multi-systemic disorder incorporating primary adrenal insufficiency (PAI), steroid resistant nephrotic syndrome and neurological dysfunction. Accumulation of sphingolipid intermediates, as seen with loss of function mutations in SGPL1, has been implicated in mitochondrial dysregulation, including alterations in mitochondrial membrane potentials and initiation of mitochondrial apoptosis. For the first time, we investigate the impact of S1P lyase deficiency on mitochondrial morphology and function using patient-derived human dermal fibroblasts and CRISPR engineered SGPL1-knockout HeLa cells. Reduced cortisol output in response to progesterone stimulation was observed in two patient dermal fibroblast cell lines. Mass spectrometric analysis of patient dermal fibroblasts revealed significantly elevated levels of sphingosine-1-phosphate, sphingosine, ceramide species and sphingomyelin when compared to control. Total mitochondrial volume was reduced in both S1P lyase deficient patient and HeLa cell lines. Mitochondrial dynamics and parameters of oxidative phosphorylation were altered when compared to matched controls, though differentially across the cell lines. Mitochondrial dysfunction may represent a major event in the pathogenesis of this disease, associated with severity of phenotype.
Keywords: Sphingolipid metabolism; Mitochondrial dynamics; Steroidogenic capacity; Oxidative phosphorylation; Sphingosine-1-phosphate lyase; ADRENAL INSUFFICIENCY; SPHINGOSINE 1-PHOSPHATE; NEPHROTIC SYNDROME; EXPRESSION; MUTATIONS; RECEPTOR; FUSION; CORTICOSTERONE; SPHINGOLIPIDS; BIOSYNTHESIS